Indonesia Diagnostic Review of Consumer Protection and Financial Literacy : Volume 2. Comparison with Good Practices - World Bank Group (World Bank, Washington, DC, 2017)
This diagnostic study was undertaken by the World Bank in response to a request from Otoritas Jasa Keuangan (OJK), the Indonesian Financial Services Authority, and Bank Indonesia, the nation’s central bank. Indonesia’s financial sector has a lot of growth potential considering the relatively low volume of domestic credit provided by the private sector - just 43 percent of gross domestic product (GDP) in 2012. To steer the growth to sustainability, the Indonesian authorities have emphasized financial consumer protection in the 5 pillars of Indonesia’s national strategy for financial inclusion. This review aims to assist Indonesia in developing and implementing its national strategy and provides a detailed assessment of the consumer protection framework in six segments of Indonesia’s financial sector: banking, securities, insurance, non-bank credit institutions, private pensions, and credit reporting. This study also informed the design of the World Bank’s support program for Indonesia under the financial inclusion support framework (FISF) initiative. The review addresses the following issues: (1) institutional arrangements, (2) legal and regulatory framework, (3) transparency and disclosure, (4) business practices, (5) complaints handling and dispute resolution mechanisms, and (6) consumer awareness and financial literacy. Volume I summarizes the key findings and recommendations and volume II assesses each financial sector segment with regard to the good practices for financial consumer protection.